Information System Architecture Planning Using Togaf Architecture Development Method - K L Putra; I D Sumitra (Peneliti.net, 2020)
The purpose of this research is to develop an existing information system by designing a service, planning, and reporting system in the Cimahi City Revenue Management Agency Identification Sector. The method used is TOGAF-ADM so that it is more flexible in verifying various types of modelling techniques used in designing information systems. The steps implemented in this design are TOGAF ADM, including Preparation, Vision Architecture, Business Architecture, Information Systems Architecture, and Technology Architecture. Output from this stage will produce an enterprise architecture that can later be used by organizations to support business processes and achieve strategic goals. The results of the analysis of the application of the TOGAF ADM method are in the form of Company Architecture modelling which provides guidance in the development of information systems in the future in the Field of Identification of the Revenue Management Agency of Cimahi.